Efeito dos tratamentos sub-zero e criogênico nas propriedades mecânicas e tribológicas do aço rápido ABNT M2 - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The steel tools have a wide scale of applications in the metal mechanics industry, ranging from matrices and drills to helical end mills. Steel tools are widely used to fabrication of cutting tools which work in high speeds and high temperatures. It’s essential that tools, when in service, be highly hard and resistant without any susceptibility to deformations under extreme conditions. The obtainment of such mechanical properties is made through heat treatment by quenching and tempering. These processes result in a microstructure with high hardness and good toughness. However steel tools are quite susceptible to retention of austenite retained during heat treatment, which isn't desirable for this type of steel. With the enhancement intention, began study of the consequences that addition of the treatments below zero would bring the steel. These treatments are known as Sub-zero and Cryogenic, be approximately -80ºC and -196ºC, respectively, the temperatures of realization of these treatments. This study aims to compare and evaluate the mechanical and tribological properties of high steel M2 when subjected to cryogenic and sub-zero treatment. The results were obtained from mechanical tests of hardness, microhardness, impact and wear, and through microstructural analysis realized by optical microscope, electron microscope and Raman spectroscopy. Tests and analyzes showed that the addition of sub-zero and cryogenic treatments benefiting the material with respect to hardness, microhardness, tenacity and carbide precipitation. These being more noticeable results on the samples that used cryogenics.
Keywords: Mechanical Engineering; Steel; Heat treatment; Cryogenics; Engenharia mecânica; Aço; Tratamento térmico; Criogenia; CNPQ::ENGENHARIAS